EUTHANASIA: AN OVERVIEW AND THE INDIAN PERSPECTIVE (Proceeding of the International Conference on Arts and Humanities, 2018)
Mercy killing or Euthanasia has involved the attention of philosophers and lawyers, since the time of Greek thinkers in the west and the Mahabharata in the east. If  we take a look at what different religions in India think about Euthanasia then we will find out that many religion favours  Euthanasia like the Hindus, Jains,etc. In India abetment of suicide and attempt to suicide are both criminal offences under Indian Penal Code 1860. Because suicide has been interpreted as inclusive of all forms of self-willed death, Euthanasia became illegal. But there is some sympathy for Euthanasia. Recently the efforts  has been made in India to repeal Section 309 of Indian Penal Code 1860 which has revived the debate of Euthanasia in the Indian perspective. The Aruna Shanbaug case initially brought the debate of Euthanasia into limelight after which the offering of mercy death to a suffering person has been greatly discussed. It has once again come to the forefront with the Government signaled its intention to do away with the section 309 IPC 1860. The present paper is an attempt to analyze Euthanasia and its overview in the Indian Perspective. In the rare circumstances death is a relief from a life of unbearable suffering, it should be encouraged.
Keywords: Mercy Killing or Euthanasia; Active Euthanasi; Passive Euthanasia; Homicide